A mechanism for lack of sea ice reversibility in the Southern Ocean. Issue 23 (11th December 2014) - Ridley, Jeff K.; Hewitt, Helene T.
Abstract: We find evidence that ocean processes during global warming may result in irreversible changes to the Antarctic sea ice, whereas the Arctic sea ice changes appear to be reversible. Increased forcing gives rise to strong heat uptake in the Southern Ocean, and existing pathways provide an increased transport of heat to the Weddell Sea. As atmospheric concentrations of CO2 are returned to preindustrial levels, the Antarctic ice extent at first recovers, but a rapid change in the position of the an ocean front in the South Atlantic maintains the heat transport into the Weddell Sea. A cooling surface initiates deep convection, accessing the stored heat, resulting in a substantial loss of sea ice, which has not recovered after a further 150 years at preindustrial CO2 . Key Points: Antarctic sea ice decline may not be reversible The ocean heat flux into the Weddell Sea is climate sensitive Deep convection in the Weddell Sea releases ocean heat store